Ultra-Wideband On-Metal Four-Antenna Module for 5G/6G/WiFi-6E IoT Mobile Device MIMO Antennas and Its Field Test Study - Kin-Lu Wong; Cheng-Hsuan Shaw; Wan-Ting Li; Wei-Yu Li (IEEE Access)
A small-size on-metal four-antenna (OM4A) module having an ultra-wide band (UWB) covering 3.3-8.4 GHz (fractional bandwidth 87.2%) for Internet-of-Things (IoT) mobile device MIMO antennas is presented. The UWB OM4A module is the first ground-backed four-antenna module that can cover the fifth-generation (5G) mid-band (3.3-5.0 GHz), future potential six-generation (6G) upper mid-band (6.425-8.4 GHz), and WiFi-6E 5/6 GHz band (5.15-7.125 GHz) for MIMO applications. The OM4A module uses a small circular patch antenna of diameter 47.5 mm (patch size $0.21λ ^{2}$ with respect to the wavelength at 3.3 GHz) and thickness 3 mm (about $0.033λ $ ) to provide four uncorrelated UWB antennas covering 3.3-8.4 GHz. To obtain four UWB antennas, the circular patch is separated into four quadrants; each quadrant is bounded by two orthogonal shorting-pin rows which function like metal walls. In addition, two orthogonal linear slots are added along the centerlines of the four quadrants. In this case, each antenna can effectively generate four resonant modes including a quarter-circle TM $_{1/2,1/2}$ -like mode, a semi-circle TM21 mode, a semi-circle TM31 mode, and a semi-circle TM41 mode to form the target UWB. By applying two OM4A modules, eight uncorrelated antennas can be provided for 5G/6G/WiFi-6E IoT mobile device MIMO applications. A field test study of using two OM4A modules as eight receive antennas in the MIMO system with four spatial streams ( $8× 4$ MIMO) is conducted in the campus public outdoor scenario. Testing results of 4.8-4.9 GHz, 6.1-6.2 GHz, and 7.025-7.125 GHz respectively in the 5G mid-band, WiFi-6E 5/6 GHz band, and 6G upper mid-band are analyzed. Details of the UWB OM4A module and MIMO field test are presented.